Screening and genome-wide analysis of lignocellulose-degrading bacteria from humic soil - Zhang, Tianjiao; Wei, Shuli; Liu, Yajie; Cheng, Chao; Ma, Jie; Yue, Linfang; Gao, Yanrong; Cheng, Yuchen; Ren, Yongfeng; Su, Shaofeng; Zhao, Xiaoqing; Lu, Zhanyuan (Frontiers in Microbiology, 2023)
Crop straw contains huge amounts of exploitable energy, and efficient biomass degradation measures have attracted worldwide attention. Mining strains with high yields of cellulose-degrading enzymes is of great significance for developing clean energy and industrial production of related enzymes. In this study, we reported a high-quality genome sequence of Bacillus velezensis SSF6 strain using high-throughput sequencing technology (Illumina PE150 and PacBio) and assessed its lignocellulose degradation potential. The results demonstrated that the genome of B. velezensis SSF6 was 3.89 Mb and contained 4,015 genes, of which 2,972, 3,831 and 158 genes were annotated in the COGs (Clusters of Orthologous Groups), KEGG (Kyoto Encyclopedia of Genes and Genomes) and CAZyme (Carbohydrate-Active enZymes) databases, respectively, and contained a large number of genes related to carbohydrate metabolism. Furthermore, B. velezensis SSF6 has a high cellulose degradation capacity, with a filter paper assay (FPA) and an exoglucanase activity of 64.48 ± 0.28 and 78.59 ± 0.42 U/mL, respectively. Comparative genomic analysis depicted that B. velezensis SSF6 was richer in carbohydrate hydrolase gene. In conclusion, the cellulose-degrading ability of B. velezensis SSF6 was revealed by genome sequencing and the determination of cellulase activity, which laid a foundation for further cellulose degradation and bioconversion.